Moving meals and migrating mothers : culinary cultures, diasporic dishes and familial foodways - Cassidy, Tanya; Tom, Abdullahi Osman El-, 1954- (Demeter Press, 2021)
Moving Meals and Migrating Mothers: Culinary cultures, diasporic dishes and familial foodways explores the complex interplay between the important global issues of food, families and migration. We have an introduction and twelve additional chapters which we have organised into three parts: Part I Moving Meals, Markets and Migrant Mothers; Part II Migrating Mothers Performing Identity through Moving Meals; Part III Meanings and Experiences of Migrant Maternal Meals. Although these parts are not mutually exclusive, they are meant to emphasize socio-cultural and economic considerations of migrati.